2020
DOI: 10.1042/bsr20200392
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-486-3p inhibits the proliferation, migration and invasion of retinoblastoma cells by targeting ECM1

Abstract: It has been reported that miR-486-3p expression is decreased in retinoblastoma (RB) tumor tissues, however, its function in RB has been less reported. The present study aimed to explore the regulatory effects of miR-486-3p on RB cells. The expression of miR-486-3p in RB tissues and cells was detected by quantitative real-time polymerase chain reaction (qRT-PCR). Cell viability, proliferation, apoptosis, migration and invasion ability were determined by cell counting kit-8 (CCK-8) kit, clone formation assay, fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Previous researches have reported that miRNAs are powerful modulators of complex biological processes, including cell growth, apoptosis, metastasis, and metabolism [ 25 ], Additionally, it was also revealed that aberrant miRNA expression was associated with the progression of many types of cancer [ 26 , 27 ], including OSCC [ 28 ]. miR-486-3p and miR-637 are well-recognized tumor suppressors [ 29 , 30 ] and have been uncovered to impede OSCC tumorigenesis [ 15 , 16 ]. In this study, a decreased miR-486-3p or miR-637 expression was observed in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have reported that miRNAs are powerful modulators of complex biological processes, including cell growth, apoptosis, metastasis, and metabolism [ 25 ], Additionally, it was also revealed that aberrant miRNA expression was associated with the progression of many types of cancer [ 26 , 27 ], including OSCC [ 28 ]. miR-486-3p and miR-637 are well-recognized tumor suppressors [ 29 , 30 ] and have been uncovered to impede OSCC tumorigenesis [ 15 , 16 ]. In this study, a decreased miR-486-3p or miR-637 expression was observed in OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…ECM1 has been proved to play an essential role in embryonic chondrogenesis ( Deckers et al, 2001 ), skin differentiation ( Mcgrath, 2015 ), epithelial cell proliferation ( Yang et al, 2020 ), Angiogenesis ( Wang B et al, 2020 ), tumorigenesis ( Wang et al, 2003 ) and other biological processes. Emerging evidence has revealed that ECM1 is upregulated in many cancers and contributes to a worse patient prognosis ( Lee et al, 2015 ; Chen et al, 2016 ; Gan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have established hsa-miR-486 to be a tumor suppressor [55]. In many cancers including OSCC, its downregulation is associated with migration and invasion [41].…”
Section: Discussionmentioning
confidence: 99%